Pengaruh Konservatisma Akuntansi, Sales Growth dan Tax Planning Terhadap Sengketa Pajak Penghasilan - Putri, Sheila Damika; Pernamasari, Rieke (Media Akuntansi Perpajakan, 2023)
Income tax disputes can occur because the calculation of the tax payable is not in accordance with tax provisions which will then trigger differences in calculations or interpretations between the taxpayer and the tax authorities as a result of issuing decisions or policies that can be appealed or sued, in this case it is strictly avoided by taxpayers because it will harm the company in the future, therefore this paper aims to examine the influence of accounting conservatism, sales growth and tax planning on income tax disputes which are thought to trigger income tax disputes in registered non-cyclicals consumer sector companies in the Indonesia Stock Exchange for the period 2017 to 2021 using the purposive sampling research method and conducting analytical tests using SPSS 25 which states that conservatism has no effect on income tax disputes so it cannot cause income tax disputes while sales growth and tax planning have an effect on income tax disputes so that it can trigger an income tax dispute.